Apakah latihan selama 4 minggu dengan menggunakan karet dapat meningkatkan kecepatan pukulan gyaku tsuki karate gokasi atlet karate berusia 16-20 tahun? - Seriannuari, Fatwa Aulia; Yono, Topo; Sulaiman, Ahmad (Universitas Nusantara PGRI Kediri, 2024)
Effective physical training is crucial for karate athletes aiming to enhance their techniques and increase the speed of their attacks, particularly gyaku-tsuki. This study investigates the impact of rubber-based exercise on the speed of gyaku-tsuki punches among Gokasi karate athletes in Jember Regency with an age range of 16-20 years, male and female. An experimental method with a one-group pretest-posttest design was employed. The population in this study were Gokasi Jember karate athletes in junior to senior classes, with a total of 12 athletes. The sampling technique used in this research is total sampling. Therefore, the entire population was taken as a sample of 12 athletes. Speed measurements of the gyaku-tsuki punch were taken both before and after the rubber training regimen. Data analysis using SPSS 21 covering descriptive analysis, normality test, and Paired sample Test. The paired sample test yielded a significance value of 0.000, which is below the 0.05 threshold. Analysis of the pre-test and post-test averages shows an increase from 30.67 to 31.92. These findings suggest that a four-week rubber training program positively affected Gyaku-Tsuki punch speed. Furthermore, the average results demonstrate an improvement in punch speed. These findings contribute to karate coaches and athletes applying rubber exercises to improve gyaku-tsuki punch speed. The findings also provide valuable insights for karate coaches and athletes, recommending the inclusion of rubber-based training in their routines to enhance the speed and effectiveness of gyaku-tsuki punches.